(untitled) (REVISTA NODO, 2013)
The article undertakes the issue of linear public spaces in Latin-American cities, understanding them as crossing points that involve leisure and amusement, casual and frivolous encounters where collective routines become the stage of city life and —as it also happens in the theater— grow to be locations to see and to be seen, spaces to identify with all social groups, places to assert the sense of community. The authoress begins by examining the words that designate urban linear public spaces such as street, sidewalk, boulevard, promenade, avenue, esplanade and seafront, and ends by analyzing recently built linear public spaces in cities like Sao Paulo, San Juan, Guayaquil, Monterrey and Nuevo Leon, in order to provide a comparative frame to make evident the general preoccupation for all things public in Latin America.